Adrenal gland volume, intra-abdominal and pericardial adipose tissue in major depressive disorder - Kahl, Kai G.; Deuschle, Michael (Psychoneuroendocrinology, 2015)
Summary: Major depressive disorder (MDD) is associated with an increased risk for the development of cardio-metabolic diseases. Increased intra-abdominal (IAT) and pericardial adipose tissue (PAT) have been found in depression, and are discussed as potential mediating factors. IAT and PAT are thought to be the result of a dysregulation of the hypothalamus-pituitary-adrenal axis (HPAA) with subsequent hypercortisolism. Therefore we examined adrenal gland volume as proxy marker for HPAA activation, and IAT and PAT in depressed patients. Twenty-seven depressed patients and 19 comparison subjects were included in this case-control study. Adrenal gland volume, pericardial, intraabdominal and subcutaneous adipose tissue were measured by magnetic resonance imaging. Further parameters included factors of the metabolic syndrome, fasting cortisol, fasting insulin, and proinflammatory cytokines. Adrenal gland and pericardial adipose tissue volumes, serum concentrations of cortisol and insulin, and serum concentrations tumor-necrosis factor-α were increased in depressed patients. Adrenal gland volume was positively correlated with intra-abdominal and pericardial adipose tissue, but not with subcutaneous adipose tissue. Our findings point to the role of HPAA dysregulation and hypercortisolism as potential mediators of IAT and PAT enlargement. Further studies are warranted to examine whether certain subtypes of depression are more prone to cardio-metabolic diseases.